RECOGNIZING MANTLE PLUMES IN THE GEOLOGICAL RECORD - Ernst R.E.; Buchan K.L. (My University, 2003)
Mantle plumes are recognized by domal uplift, triple junction rift-ing, and especially the presence of a large igneous province (LIP), dominated in the Phanerozoic by flood basalts, and in the Proterozoic by the exposed plumbing system of dykes, sills, and layered intrusions. In the Archean, greenstone belts that contain komatiites have been linked to plumes. In addition, some carbonatites and kimberlites may originate from plumes that have stalled beneath thick lithosphere. Geochemistry and isotopes can be used to test and characterize the plume origin of LIPs. Seismic tomography and geochemistry of crustal and subcrustal xenoliths in kimberlites can identify fossil plumes. More speculatively, plumes (or clusters of plumes) have been linked with variation in the isotopic composition of marine carbonates, sea-level rise, iron formations, anoxia events, extinctions, continental breakup, juvenile crust produc-tion, magnetic superchrons, and meteorite impacts. The central region of a plume is located using the focus of a radiating dyke swarm, the distribution of komatiites and picrites, etc. The outer boundary of a plume head circumscribes the main flood basalt distribution and approximately coincides with the edge of domal uplift that causes shoaling and offlap in regional sedimentation.
Keywords: large igneous province (LIP); FOZO; isotope; rift; dyke swarm; mantle root